ВУЗОВСКОЕ ДОПОЛНИТЕЛЬНОЕ ОБРАЗОВАНИЕ В САРАТОВСКОЙ ОБЛАСТИ - Ташпеков, Г.А. (My University, 2019)
Аннотация В современных условиях дополнительное профессиональное образование (ДПО) выступает одним из главных элементов системы непрерывного образования. В статье анали- зируется институциональная и организационная структура ДПО высших учебных заведений Саратовской области, формирование и развитие которой определяет Федеральный закон «Об образовании в РФ» от 29.12.2012 №273-ФЗ. Рассмотрены основные тенденции развития системы дополнительного профессионального образования вузов в Саратовской области. Abstract In modern conditions, additional vocational education (VET) is one of the main elements of the system of continuing education. The article analyzes the institutional and organizational structu- re of vocational education in higher educational institutions of the Saratov region, the formation and development of which is determined by the Federal Law «On Education in the Russian Federation» dated December 29, 2012 No. 273-FZ. The main trends in the development of the system of additional professional education of universities in the Saratov region are considered.
Additional professional education in the universities of the Saratov region
Keywords: дополнительное профессиональное образование; институциональная структура; вузы; Саратовский национальный исследовательский государственный университет имени Н.Г. Чернышевского; реформирование сферы образования; additional professional education; institutional structure; universities; Saratov Na- tional Research State University named after NG Chernyshevsky; education reform